Mechanisms of dsRNA virus replication: Cloning, production and structural characterization of C-terminal domain of sigmaNS. - Manoczki, Nelli Vanessza (Jihočeská univerzita, 2019)
A gene fragment encoding the C-terminal domain of the sigmaNS protein of the avian reovirus was amplified via PCR. The amplicon was cloned using BsaI restriction enzyme into the pASKIBA37+ expression vector and transformed into One ShotTM TOP 10 Chemically Competent E.coli cells. Colony PCR was performed and plasmids were sent for sequencing. Sequence verified plasmids were transformed into One ShotTM BL21 (DE3) or Rosetta-gami B (DE3) Chemically Competent E.coli cells. During Pilot expressions the conditions for production of soluble recombinant protein were optimized and according to them the recombinant protein was produced in large scale. The presence of the sigmaNS-terminal domain was verfied by Western Blot.
Mechanisms of dsRNA virus replication: Cloning, production and structural characterization of C-terminal domain of sigmaNS.